Extremophilic Oxidoreductases for the Industry: Five Successful Examples With Promising Projections - Espina, Giannina; Atalah, Joaquín; Blamey, Jenny M. (Frontiers in Bioengineering and Biotechnology, 2021)
In a global context where the development of more environmentally conscious technologies is an urgent need, the demand for enzymes for industrial processes is on the rise. Compared to conventional chemical catalysts, the implementation of biocatalysis presents important benefits including higher selectivity, increased sustainability, reduction in operating costs and low toxicity, which translate into cleaner production processes, lower environmental impact as well as increasing the safety of the operating staff. Most of the currently available commercial enzymes are of mesophilic origin, displaying optimal activity in narrow ranges of conditions, which limits their actual application under industrial settings. For this reason, enzymes from extremophilic microorganisms stand out for their specific characteristics, showing higher stability, activity and robustness than their mesophilic counterparts. Their unique structural adaptations allow them to resist denaturation at high temperatures and salinity, remain active at low temperatures, function at extremely acidic or alkaline pHs and high pressure, and participate in reactions in organic solvents and unconventional media. Because of the increased interest to replace chemical catalysts, the global enzymes market is continuously growing, with hydrolases being the most prominent type of enzymes, holding approximately two-third share, followed by oxidoreductases. The latter enzymes catalyze electron transfer reactions and are one of the most abundant classes of enzymes within cells. They hold a significant industrial potential, especially those from extremophiles, as their applications are multifold. In this article we aim to review the properties and potential applications of five different types of extremophilic oxidoreductases: laccases, hydrogenases, glutamate dehydrogenases, catalases and superoxide dismutases. This selection is based on the extensive experience of our research group working with these particular enzymes, from the discovery up to the development of commercial products available for the research market.